Textile-Scale Liquid–Metal Fibers with Strain-Invariant Conductivity Enable Absorption-Enhanced EMI Shielding - Li, Ruosong; Tao, Ruyi; Huangfu, Youpeng; Bai, Zhongyi; Wei, Liping; Yan, Yuan; Zhang, Rui; Fan, Daidi; Zhao, Biao (Nano-Micro Letters, 2026)
Conventional conductive elastomeric composites, consisting of conductive fillers dispersed in elastomers, are widely used in soft electronics for strain sensing via resistance changes arising from filler separation during elongation. However, they often exhibit substantial performance degradation under large strains. Liquid metals (LMs) have recently attracted significant attention owing to their unique fusion of metallic conductivity and fluidic properties. Here, we develop sheath–core fibers featuring a magnetic LM (MLM) core, formed by embedding Fe particles into eutectic gallium–indium alloy (EGaIn) dispersed in thermoplastic polyurethane (TPU), and coaxially wet-spun with an insulating TPU sheath. Subsequently, these MLM/TPU fibers are woven into horizontally and vertically interlaced textiles. This wet-spinning process, coupled with post-freeze-pressure activation, fuses Fe-EGaIn droplets into percolating networks, yielding exceptional conductivity (3.9 × 104 S m−1), extreme stretchability (482% elongation), and strain-invariant resistance ( − 6% at 100% strain). Particularly at 7 wt% Fe, the MLM/TPU composite serves as a magnetically responsive, reconfigurable conductor that enables tunable Joule heating (reaching 75.8 °C at 1.2 V), infrared stealth, and magnetically driven remote switching, while promoting absorption-dominated electromagnetic interference (EMI) shielding (33.82 dB with an absorptivity of 0.520). This study offers substantial promise for applications in wearable electronics, soft robotics, and EMI-shielding textiles. Highlights: 1 A Fe-EGaIn/TPU core–sheath fiber is fabricated by coaxial wet spinning, enabling high stretchability together with Joule heating, infrared stealth, strain-invariant conductivity, and electromagnetic interference (EMI) shielding. 2 The fiber exhibits strain-invariant conductivity, showing only a -6% resistance change at 100% strain; COMSOL simulations corroborate the tensile-loading mechanism underpinning this behavior. 3 A Fe-EGaIn/TPU textile woven from orthogonally interlaced horizontal and vertical fibers delivers absorption-dominated EMI shielding with only 7 wt% Fe.